Identification of synonymous constraint elements in the protein-coding region of dengue serotype 2 quasispecies from next generation sequencing data - GALARION, MA. JOWINA (Archīum Ateneo, 2018)
This study used bioinformatics tools to systematically identify synonymous constraint elements (SCEs) in the dengue serotype 2 quasispecies, which are signatures of probable overlapping functional elements in the viral genome. Sequencing data used in the analysis was generated using next generation sequencing of isolated virus from dengue-positive clinical sera. The analysis was done using a standard in-house analysis pipeline performing data quality check, pre-processing, genome assembly and quasispecies reconstruction. The search for SCEs was done using the program FRESCo. Most of the significant SCEs identified were located at the non-structural region of the genome, NS5 harboring the most. Within the structural region, only the envelope gene has significant SCEs recovered. The study demonstrates the feasibility of systematically identifying SCEs using quasispecies alignment. Although parts of the NS5 gene harbor putative functional elements, other SCEs identified here that has not yet been described can serve as initial information to do site-directed mutagenesis studies. Finally, the highly conservative nature of SCEs may serve as excellent targets for antiviral drug designs.